Horses, Lakes, and Heroes: Landnámabók S83, Vǫlsunga saga 13, and the Grey of Macha - Egeler, Matthias (Viking and medieval Scandinavia, 2014)
Landnámabók contains an anecdote about Auðun stoti, ‘the Stutterer’, an early Icelandic settler, who encounters a magnificent grey horse that emerges from and ultimately returns to a lake on the Snafellsnes peninsula. Certain key characteristics of this horse recall Grani, the horse of the hero Sigurðr. Auðun’s family connections point beyond a purely Norse context, however. Landnámabók claims that Auðun was married to the daughter of an Irish king and even quotes a genuine Irish name for both his wife and probably also his father-in-law. This makes it noteworthy that the core characteristics of Auðun’s ‘lake-horse’ not only invoke images of Grani, but also directly parallel accounts of the Grey of Macha, the horse of the hero Cú Chulainn in Irish tales of the Ulster Cycle. This article discusses the value of the anecdote about Auðun’s ‘lake-horse’ for the understanding of Irish-Norse cultural relationships.